Protocadherin-1 is essential for cell entry by New World hantaviruses. (22nd November 2018) - Jangra, Rohit; Herbert, Andrew; Li, Rong; Jae, Lucas; Kleinfelter, Lara; Slough, Megan; Barker, Sarah; Guardado-Calvo, Pablo; Román-Sosa, Gleyder; Dieterle, M.; Kuehne, Ana; Muena, Nicolás; et al.
Abstract The zoonotic transmission of hantaviruses from their rodent hosts to humans in North and South America is associated with a severe and frequently fatal respiratory disease, hantavirus pulmonary syndrome (HPS)1, 2 . No specific antiviral treatments for HPS are available, and no molecular determinants of in vivo susceptibility to hantavirus infection and HPS are known. Here we identify the human asthma-associated gene protocadherin-1 (PCDH1 )3–6 as an essential determinant of entry and infection in pulmonary endothelial cells by two hantaviruses that cause HPS, Andes virus (ANDV) and Sin Nombre virus (SNV). In vitro, we show that the surface glycoproteins of ANDV and SNV directly recognize the outermost extracellular repeat domain of PCDH1—a member of the cadherin superfamily7, 8 —to exploit PCDH1 for entry. In vivo, genetic ablation ofPCDH1 renders Syrian golden hamsters highly resistant to a usually lethal ANDV challenge. Targeting PCDH1 could provide strategies to reduce infection and disease caused by New World hantaviruses. New World hantaviruses—which cause a severe human respiratory disease—use surface glycoproteins to bind to the human protocadherin-1 protein and enter endothelial cells in vitro; depleting protocadherin-1 in Syrian golden hamsters largely protects against disease.